Characterization and phylogenetic analysis of the first complete mitochondrial genome sequence of three Artocarpus species in Hainan Province - Wang, Huanwei; Fan, Hongyan; Qin, Yuhong; Wu, Chunmei; Zhao, Ya; Justice, Norvienyeku; Xiao, Min; Li, Shaoka; Miao, Weiguo; Liu, Wenbo (Frontiers in Plant Science, 2025)
The Artocarpus genus, belonging to the Moraceae family, exhibits various pharmacological and biological functions. However, the mitochondrial DNA (mtDNA) of Artocarpus species remains largely unexplored, which hampers our understanding of its phylogenetic classification as well as population identification. In this study, we completely sequenced and assembled the mtDNA of three Artocarpus species, including Artocarpus heterophyllus, A. heterophyllus(R), and A. integer. Three Artocarpus species exhibited highly similar mtDNA features, with mtDNA sizes of approximately 438,620 bp, consisting of six contigs, and included 32 different protein-coding genes (PCGs). The codon usage analysis demonstrated that Leucine and Serine were the most preferred amino acids in three Artocarpus species. Furthermore, in three Artocarpus species mt genomes, 9 homologous fragments were found to transfer from the cp genome, which contain complete psaB, psaA, ndhB and rps7 genes. Phylogenetic trees further reveal that three Artocarpus species are most closely related to Ficus carica and Morus notabilis. In summary, this study fills the gap in mitochondrial genome data within the Artocarpus genus and provides a theoretical foundation for further understanding the taxonomic classification within Artocarpus species.